2016
DOI: 10.1089/dia.2015.0159
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Insulin Pump Therapy on Glycemic Profiles in Patients with Type 2 Diabetes: Data from the OpT2mise Study

Abstract: Background: The OpT2mise randomized trial was designed to compare the effects of continuous subcutaneous insulin infusion (CSII) and multiple daily injections (MDI) on glucose profiles in patients with type 2 diabetes.Research Design and Methods: Patients with glycated hemoglobin (HbA1c) levels of ≥8% (64 mmol/mol) and ≤12% (108 mmol/mol) despite insulin doses of 0.7–1.8 U/kg/day via MDI were randomized to CSII (n=168) or continued MDI (n=163). Changes in glucose profiles were evaluated using continuous glucos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
0
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 31 publications
(38 citation statements)
references
References 29 publications
3
34
0
1
Order By: Relevance
“…Important information was provided by data from the OpT2mise study; blinded CGM data were available for patients treated by CSII and MDI. Although a reduction in exposure to hyperglycemia in the CSII group was demonstrated, it was not associated with an increase in time spent in the hypoglycemic range (glucose levels < 70 mg/dL) . CSII treatment is not associated with elevated risk for hypoglycemic episodes.…”
Section: Potential Barriers To Csii Therapy In Patients With T2dmentioning
confidence: 81%
“…Important information was provided by data from the OpT2mise study; blinded CGM data were available for patients treated by CSII and MDI. Although a reduction in exposure to hyperglycemia in the CSII group was demonstrated, it was not associated with an increase in time spent in the hypoglycemic range (glucose levels < 70 mg/dL) . CSII treatment is not associated with elevated risk for hypoglycemic episodes.…”
Section: Potential Barriers To Csii Therapy In Patients With T2dmentioning
confidence: 81%
“…17 In the present work, we demonstrate that the BHG contribution predominates across a large range of HbA1c levels, from <8% 14 Their profiles were characterized by an elevated 24-hour mean glucose concentration, although the basal and postprandial hyperglycaemic components were not characterized.…”
Section: Effect Of Csii Therapy On Changes In Hba1c and Basal And Pmentioning
confidence: 50%
“…[14][15][16][17] In this post hoc analysis, data from the OPT2mise study were used to perform different evaluations on BHG and PPHG ( Figure S1). Briefly, patients with poor glycaemic control while undergoing MDI therapy (n = 495) were enrolled in an 8-week run-in period for insulin dose optimization (≥0.7 and ≤1.8 U/kg/d).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although multiple daily injections (MDI) and continuous subcutaneous insulin infusion (CSII) are 2 intensive insulin therapy methods in patients with type 2 diabetes, studies indicated an advantage in glycated haemoglobin (HbA1c) decrease and less daily insulin use in CSII when compared with MDI even though no difference was found between the 2 therapies in hypoglycaemic episode . Therefore, how to decrease the glucose fluctuation and hypoglycaemic episode at the same time of reducing HbA1c level becomes an essential part in intensive insulin therapy.…”
Section: Introductionmentioning
confidence: 99%